Pengaruh Pengeluaran Pemerintah di Sektor Pendidikan dan Kesehatan Terhadap Indeks Pembangunan Manusia di 16 Negara Organisasi Konfrensi Islam (OKI) - Al Asy Ari Adnan Hakim; Raditya Sukmana (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
The purpose of this study is to examine and analyze the role of government as reflected ingovernment spending in the education and health sectors to Human Development Index(HDI) in 16 OIC Countries. The data used in this study secondary data in the form of paneldata conducted on 16 countries OKI in the period 2008 s/d 2011 which then analyzed withmultiple linear regression analysis tools. The results showed that government expendituresin the education sector and government expenditures in the health sector had aninsignificant negative effect on the Human Development Index (HDI) in 16 OIC States.